IN VITRO ANTIBACTERIAL EFFECT OF DIODE LASER ON Porphyromonas gingivalis ASSOCIATED WITH PERIODONTITIS - Dwi Wahyu Indrawati; Anis Khoirin Hayati; Rizky Briliant Syah Manurung; Muhammad Rizky Akbar Manurung; Agus Hayatal Falah (Journal of Vocational Health Studies, 2026)
Background: Antibiotic resistance has become a major global health concern, including in periodontal therapy. Therefore, alternative antimicrobial approaches that do not rely on antibiotics are required. Purpose: This study aims to evaluate the in vitro antibacterial effect of the diode laser on Porphyromonas gingivalis associated with periodontitis. Method: This study employed an in vitro experimental design with a control group and a treatment group. A diode laser with a wavelength of 660 - 900 nm was applied to the P. gingivalis cultures with exposure times of 5, 10, and 15 seconds. The bacterial growth was assessed by measuring the inhibition zone diameter. Result: The results demonstrated a significant reduction in P. gingivalis growth following diode laser irradiation, with longer exposure times producing larger inhibition zones. Conclusion: Diode laser irradiation exhibited significant in vitro antibacterial activity against P. gingivalis. These findings indicate that diode lasers have potential as an alternative antimicrobial modality in periodontal therapy and warrant further investigation through in vivo and clinical studies.